Dealing with Disasters from Early Modern to Modern Times : Cultural Responses to Catastrophes - Jensen, Lotte; van Asperen, Hanneke (Book collections on Project MUSE., 2023)
Disasters are as much cultural as natural phenomena. For centuries, news about catastrophic events has been disseminated through media such as chronicles, pamphlets, newspapers, poems, drawings, and prints. Nowadays, we are overwhelmed with news about the cataclysmic effects of recent forest fires, floods, and storms. Due to the ongoing climate crisis, extreme weather events will likely have ever greater impacts on our lives. This volume addresses cultural representations of catastrophes such as floods, epidemics, and earthquakes over the centuries. In the past as now, artists and authors try to make sense of disasters, grasp their impact, and communicate moral, religious, or political messages. These creations reflect and shape how people learn and think about disasters that occur nearby or far away, both in time and space. The parallels between past and present underline how this book contributes to modern debates about cultural and creative strategies in response to disasters.